Acupuncture Care for Myalgia Patients at Iryas Cisauk Clinic - Dewanto Dwi Saputra; Chantika Mahadini; Ikhwan Abdullah (CV. Publikasi Indonesia, 2026)
Myalgia is a common musculoskeletal disorder characterized by muscle pain and discomfort, often caused by excessive activity, poor posture, or stress. In Traditional Chinese Medicine (TCM), acupuncture is used to regulate Qi and Xue flow to relieve pain and improve body function. This research aims to determine the benefits of acupuncture care in overcoming pain in the shoulder and neck area in myalgia patients at the Iryas Cisauk Health Clinic. This research used a qualitative descriptive design with a case study approach in one myalgia patient. Data collection was carried out through anamnesis, physical examination, and examinations based on TCM principles such as pulse and tongue examinations. Pain intensity was measured using the Numerical Rating Scale (NRS). Acupuncture therapy is administered during eight sessions of visits, and evaluations are carried out at each session to see the progression of the patient's condition. The results showed significant improvement after acupuncture therapy. The patient's pain scale decreased from NRS 6 to 0–1 after eight therapy sessions. In addition, there is an increase in the range of motion in the neck and shoulders, a reduction in pain points, and an improvement in daily activities and the quality of sleep of patients. Acupuncture care provided in a structured manner based on the diagnosis of TCM syndrome is effective in reducing myalgia pain, improving movement function, and helping the patient's condition recover. Acupuncture therapy can be a safe and beneficial alternative to non-pharmacological therapy in the treatment of musculoskeletal pain.